2023
DOI: 10.32394/rpzh.2023.0242
|View full text |Cite
|
Sign up to set email alerts
|

Radon – occurrence and impact on the health

Abstract: Radon is noble, monatomic, radioactive, heavier than the air gas. It is colorless, odorless, tasteless. It exists in natural environment as a result of the decay of radium, and emits mainly alpha radiation and less beta radiation. Residential radon concentrations vary widely by geographic area. The higher concentration of radon is expected globally in the grounds where uranium, radium and thoron are present. Radon may gather in caves, tunnels, mines as well as in other lowestlying spaces, such as basements, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…During respiration, tiny α-radioactive particles produced by radon decay can deposit on the cells lining the airways, potentially causing oxidative damage to cellular DNA, thus disrupting lung cell function and leading to lung cell damage and cancer initiation. However, the specific pathogenic mechanism of LC induced by residential radon exposure remains unclear (Wu et al, 2021;Xin et al, 2022;Dobrzynska et al, 2023;Wang et al, 2023). The results of this study indicated that the burden of LC caused by residential radon exposure in China steadily increased over the past 30 years.…”
Section: Discussionmentioning
confidence: 77%
“…During respiration, tiny α-radioactive particles produced by radon decay can deposit on the cells lining the airways, potentially causing oxidative damage to cellular DNA, thus disrupting lung cell function and leading to lung cell damage and cancer initiation. However, the specific pathogenic mechanism of LC induced by residential radon exposure remains unclear (Wu et al, 2021;Xin et al, 2022;Dobrzynska et al, 2023;Wang et al, 2023). The results of this study indicated that the burden of LC caused by residential radon exposure in China steadily increased over the past 30 years.…”
Section: Discussionmentioning
confidence: 77%
“…We posit that concomitant resistance in cancer, and its proposed mechanisms of action, can be explained as a hormesis response. Hormesis is a biphasic dose response in which a stimulus has a positive and/or stimulatory effect at low dosages and a negative, inhibitory, and/or toxic effect at higher dosages [ 12 , 13 , 14 , 15 ]. The observation that low dose radiation is possibly beneficial in certain circumstances is a classic example of the hormesis response [ 13 ].…”
Section: Cancer Hormesismentioning
confidence: 99%
“…Atravesaron muchos problemas económicos y para tener más ingresos llegaron a tener un dormitorio para estudiantes en su apartamento familiar. Para poder rentar más dormitorios, María dormía en el sillón del comedor y se levantaba todos los días a las seis de la mañana para preparar el desayuno 4,5 . Cuando ella tenía 4 años su madre se enfermó de tuberculosis.…”
Section: Dejemos De Temer a Aquello Que Se Ha Aprendido A Entenderunclassified